Does Daylight Saving Save Energy? A Meta-Analysis - Tomáš Havránek; Dominik Herman; Zuzana Irsova (Charles University in Prague, Institute of Economic Studies (IES), 2016)
The original rationale for adopting daylight saving time (DST) was energy savings. Modern research studies, however, question the magnitude and even direction of the effect of DST on energy consumption. Representing the first meta-analysis in this literature, we collect 162 estimates from 44 studies and find that the mean reported estimate indicates modest energy savings: 0.34% during the days when DST applies. The literature is not affected by publication bias, but the results vary systematically depending on the exact data and methodology applied. Using Bayesian model averaging we identify the most important factors driving the heterogeneity of the reported effects: data frequency, estimation technique (simulation vs. regression), and, importantly, the latitude of the country considered. Energy savings are larger for countries farther away from the equator, while subtropical regions consume more energy because of DST.
Keywords: C42; Q48; 330; Daylight saving time; energy savings; Bayesian model averaging; metaanalysis; publication bias